106 Cancer incidence and mortality in agricultural cohorts in the AGRICOH consortium. (11th October 2013) - Denholm, R E; Freeman, Beane; Schüz,; Alavanja,; MacFarlane,; Sim,; Lebailly,; Baldi,; Kjaerheim,; Langseth,; Nordby,; Park,; et al.
Abstract : Objectives: Farmers have different cancer incidence and mortality patterns than the general population, with excesses of some cancers (e.g., lymphoma, multiple myeloma, brain, skin and prostate), and lower risk of others (e.g., lung). AGRICOH, a consortium of 27 cohort studies in agricultural populations, was formed to investigate the impact of specific occupational, environmental and lifestyle factors on health outcomes in farming populations. This study aims to describe the cohort-specific cancer incidence and mortality rates in AGRICOH studies with cancer information. Methods: Outcome data have been obtained from linkage to cancer and mortality registries. Person-years of follow-up contributed by each participant will be calculated and grouped into 5-year age intervals and calendar years. Crude and age- and gender- standardised incidence and mortality rates will be estimated for each cohort, for all cancers, individual cancer sites and, where possible, specific histological subtypes. Rates will be stratified by participant's relationship to the farm (farmer, spouse) and primary commodity produced (crop, livestock or both). Results: Seven AGRICOH cohorts with cancer data have agreed to participate (n = 315, 298). These cohorts represent Australia (Pesticide Exposed Workers & Victorian Grain Farmers), France (Agriculture & Cancer), Korea (Korean Multi-Center Cancer), Norway (Cancer in the Norwegian Agricultural Population), and USA (United States Agriculture Health Study & The Marshfield Epidemiology Study Area Farm Cohort). Target populations vary between studies and include active and retired agricultural workers, farm owners and their families, and agricultural groups exposed to specific agents. Conclusions: Comparing and contrasting patterns of cancer incidence and mortality in studies from around the world with different agricultural practices and populations will generate hypotheses for future data-pooling projects. In particular, the study will identify cancers of high priority in agricultural workers and provide hypotheses on potential causes for differences in rates between populations, or on common exposures that might contribute to similarities.